Cultivares de feijão comum submetidas à inoculação de sementes com diferentes estirpes de rizóbio e doses de nitrogênio - Vitorino, Mariela Thim (2015)
Studies with rhizobia strains with high symbiotic potential, previously selected and recommended strains for production of commercial inoculants in Brazil become of great importance to obtaining increases in nodulation, biological fixation of nitrogen and yield of common bean in tropical conditions. Thus, the present study aimed to evaluate the response of common beans subjected to inoculation with strains of Rhizobium sp. and nitrogen fertilization, analyzing aspects related to nodulation of plants and grain yield in three genotypes of crops in the rainy season 2012/2013, 2013/2014 and the dry season 2013. The design was split plot in sub factorial 4 X 4 X 3 (Growing X Strain X Dose ), with four replications,, consisting of combinations of inoculation with UFLA 02-127 of R. leguminosarum bv. phaseoli, SEMIA 4077 (CIAT 899 = BR 322) of R. tropici and without inoculation and nitrogen fertilization performed with three N rates (0, 20, 60 and 80 kg ha-1). Inoculation of seeds was immediately before sowing with peat inoculant and nitrogen fertilization was performed using as source of N as urea, being divided doses at sowing and coverage (V4). The characteristics evaluated were: number of nodules, nodule dry weight, shoot dry mass, content and accumulation of nitrogen in shoots, number of pods per plant, number of grains per pod, weight, 100 grains, yield, content of nitrogen and grain nitrogen accumulation in the grain. The common bean genotypes submitted to inoculation with Rhizobium sp. and nitrogen fertilization had different responses, showing that the IPR 139 and IPR Campos Gerais cultivars have greater potential to nodulation compared cultivars IPR Tangará and IPR Andorinha. It has been found yet, nitrogen fertilization, increasing N rates up to a dose 60kg / ha-1, increasingly influenced grain yield in cultivars inoculated with strain CIAT 899.